Development of experiential learning-based tools to enhance students creative thinking in quadrilaterals and triangles - Dewi, Sri Intan Retno; Suanto, Elfis; Solfitri, Titi (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
The limited availability of supplementary mathematics learning resources aligned with the 2013 Curriculum motivated this study. The objective was to develop learning tools comprising a syllabus, lesson plans, and student worksheets on the topics of quadrilaterals and triangles for seventh-grade SMP/MTs students, using an experiential learning approach to enhance their creative thinking abilities. This research employed the 4D development model, consisting of the define, design, develop, and disseminate phases. Data were collected through questionnaires, observations, and interviews. The research instruments included validation sheets and practicality questionnaires. Expert validation indicated high levels of validity, with average scores of 3.56 for the syllabus, 3.70 for the lesson plans, and 3.67 for the student worksheets. Student worksheets were also found to be highly practical, as reflected in student response scores of 3.48 in large group trials and 3.51 in small group trials. These findings confirm that the developed mathematics learning tools are both valid and practical for use by seventh-grade students in SMP/MTs.